2022
DOI: 10.1055/s-0040-1715426
|View full text |Cite
|
Sign up to set email alerts
|

Four-Corner Arthrodesis versus Proximal Row Carpectomy: Risk Factors and Complications Associated with Prolonged Postoperative Opioid Use

Abstract: Introduction This article compares opioid use patterns following four-corner arthrodesis (FCA) and proximal row carpectomy (PRC) and identifies risk factors and complications associated with prolonged opioid consumption. Materials and Methods The PearlDiver Research Program was used to identify patients undergoing primary FCA (Current Procedural Terminology [CPT] codes 25820, 25825) or PRC (CPT 25215) from 2007 to 2017. Patient demographics, comorbidities, perioperative opioid use, and postoperative complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Risk factors for complications or reoperation following 4CF have previously been studied. Work by van Hernen et al 32 and Li et al 33 identified preoperative narcotic use, history of manual labor, and the absence of AIN/PIN neurectomy to be risk factors for complications or reoperation following 4CF. Neither of these studies addressed the role of oral corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for complications or reoperation following 4CF have previously been studied. Work by van Hernen et al 32 and Li et al 33 identified preoperative narcotic use, history of manual labor, and the absence of AIN/PIN neurectomy to be risk factors for complications or reoperation following 4CF. Neither of these studies addressed the role of oral corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…We included multiple patient baseline demographic factors, such as age, sex, BMI, and tobacco use, as these characteristics have been associated with increased or prolonged opioid use after hand procedures. 23 , 25 , 26 , 27 …”
Section: Methodsmentioning
confidence: 99%